Pengelolaan Pendidikan Dan Kewirausahaan Dalam Pendidikan Agama Islam - Arif Arif; Darul Ilmi (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
Islamic Religious Education is considered the main pillar in shaping the character of Muslims; however, in the era of globalization, entrepreneurship has become essential. The integration of entrepreneurship enables students to connect religious values with the real world, develop self-potential, and become agents of positive change. Inclusive management of Islamic religious education towards entrepreneurship is not only a necessity but also a challenge to create innovative curricula. This study employs a qualitative descriptive method through a literature review approach to examine the management of education and entrepreneurship in Islamic religious education. The goal of Islamic Religious Education is to shape individuals with profound knowledge of Islamic teachings, capable of applying them in daily life, fostering love and obedience to Allah SWT, imparting Islamic values and ethics, and encouraging critical, analytical skills, and entrepreneurial spirit. Entrepreneurship in Islamic religious education aims to mold a younger generation of Muslims who can become successful entrepreneurs and are morally and ethically responsible. The integration of entrepreneurship involves teaching entrepreneurial values and principles, as well as developing entrepreneurial skills such as creativity and management. A conducive environment for entrepreneurship, including the empowerment of micro, small, and medium-sized enterprises (UMKM), training, mentoring, access to financing, and incentives for entrepreneurs, is deemed essential. By integrating entrepreneurship into Islamic religious education, it is expected that students can prepare themselves to face the challenges of the job market and contribute to the welfare of society.